Initial impacts of the Ticket to Work program: Estimates based on exogenous variation in Ticket mail months - David Stapleton; Arif Mamun; Jeremy Page (IZA Journal of Labor Policy, 2014)
This paper presents results from an impact analysis of the Ticket to Work (TTW) program, as implemented by the Social Security Administration (SSA) from 2002 through 2007. For new, young Social Security Disability beneficiaries, we use exogenous variation in the month of Ticket mailing to rigorously estimate impacts of TTW on beneficiary outcomes over a 48-month period following the start of Ticket mailings in the beneficiary's state. We find substantial impacts on enrollment for employment services with TTW-qualified providers, but no consistent evidence of impacts on the number of months in which beneficiaries did not receive benefits because of work, or on other outcomes.
Keywords: H55; I38; 330; Ticket to Work; Social Security disability benefits; Impact analysis; Voucher; Employment services